2012
DOI: 10.1037/a0025280
|View full text |Cite
|
Sign up to set email alerts
|

The Hispanic Stress Inventory—Adolescent Version: A culturally informed psychosocial assessment.

Abstract: A 2-phase study was conducted to develop a culturally informed measure of psychosocial stress for adolescents, the Hispanic Stress Inventory-Adolescent Version (HSI-A). Phase I involved item development through the collection of open-ended focus group interview data (n=170) from a heterogeneous sample of Hispanic youth residing in the southwest and northeast United States. Phase 2 examined the psychometric properties of the HSI-A (n=1651) involving the use of factor analytic procedures to determine the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 49 publications
2
96
0
1
Order By: Relevance
“…To the degree that both parents and children utilize dual frames of reference to make sense of one another's attitudes and behaviors, parent-child conflict may be rooted in parallel dual frames of reference (Qin, 2006). Likewise, acculturation scholars have explained parent-child conflict among Latino families as the product of cultural (i.e., acculturation) gaps (Bámaca-Colbert & Gayles, 2010;Cervantes, Fisher, Córdova, & Napper, 2012;Szapocznik & Kurtines, 1993). Various types of parent-child acculturation gaps have been identified (for a review, see Telzer, 2011).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…To the degree that both parents and children utilize dual frames of reference to make sense of one another's attitudes and behaviors, parent-child conflict may be rooted in parallel dual frames of reference (Qin, 2006). Likewise, acculturation scholars have explained parent-child conflict among Latino families as the product of cultural (i.e., acculturation) gaps (Bámaca-Colbert & Gayles, 2010;Cervantes, Fisher, Córdova, & Napper, 2012;Szapocznik & Kurtines, 1993). Various types of parent-child acculturation gaps have been identified (for a review, see Telzer, 2011).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Acculturation perspectives on parent-child conflict also suggest that among families headed by parents who are immigrants or the adult children of immigrants (i.e., parents of immigrant background, PIB) the dynamics of cultural adaptation often lead to discrepant dual frames of reference (i.e., parallel dual frames of reference; Qin, 2006) and acculturation gaps (Szapocznik & Kurtines, 1993). Some research suggests that such cultural discrepancies might become sources of parent-child conflict (Bámaca-Colbert & Gayles, 2010;Cervantes, Fisher, Córdova, & Napper, 2012;Szapocznik & Kurtines, 1993). Parent-child conflict is relevant to family science because it shapes parent-child relationships, parenting practices, family dynamics, and developmental outcomes (Prado et al, 2010;Santisteban, Coatsworth, Briones, Kurtines, & Szapocznik, 2012).…”
mentioning
confidence: 99%
“…1 Higher levels of stress across the eight domains were related to heightened rates of internalizing (e.g., depression, anxiety) and externalizing (e.g., conduct problems) behaviors. 1 The relationship between these cultural stress domains and suicidality, however, has not been explored. Thus, the purpose of the current study was to; a) document the presence of suicidal ideation and self-harm behavior among Hispanic adolescents in a large four site, representative sample, b) determine gender differences in these symptoms, and c) to investigate the utility of the Hispanic Stress Inventory- Adolescent Version in identifying specific stressors that can predict self- harm in this high risk population.…”
Section: Introductionmentioning
confidence: 95%
“…A number of studies have found that Latino adolescents are the target of anti-immigrant and anti-Latino attitudes and negative public references toward their ethnic identity. 1,15 The literature details descriptions of the often traumatic immigration processes which could include life-threatening circumstances and being forced to leave family members behind in their country of origin 20 with possible impacts on suicidal behavior. 21 Mena, Santisteban, Mason and Mitrani 22 found that parent-child separations resulting from immigration have been linked to depression, particularly in Latinas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation